THE CONCEPT OF DECORUM, 'UTILE ET DULCE', AND RELIGIOUS ASPECTS IN KUNTOWIJOYO'S 'KHOTBAH DI ATAS BUKIT' NOVEL - Erfina Nuryusticia (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2021)
The aim of this study is to find the concept of decorum in Horaceâ€™s theory, that is te actions of teaching and delighting, as reflected in Khotbah di Atas Bukit (Preach on the Top ofÂ  the Hill) novel written by Kuntowijoyo. This is carried out by searching for the concepts of politeness combined with religious aspects to make the readers interested and able to take the lessons from the story to be applied in their daily lives. The search for ultimate peace of life regarding freedom that is thought to have been shackled by thoughts, memories and ideals.Â